Export and Performance Analysis of Indonesian Palm Oil Companies Facing Sustainability Policies in The European Markets Using PLS-SEM - Khoirul Anam; Achmad Fauzi; Hamidah Hendrarini; Maroeto (Postgraduate, University of Mataram, 2025)
The primary goal of this research is to investigate the effect of the European Union's Renewable Energy Directive (RED) on the financial performance and overall value of palm oil businesses in Indonesia. Since this directive has established substantial non-tariff hurdles and generated market instability for these companies, a thorough examination of its direct impacts is required. This article confronts the issue by examining the influence external factors, such as macroeconomic conditions and export levels, alongside internal corporate strategies like risk management and sustainability reporting, on the overall value of a company. The research constructs and validates a model to determine how sustainability management can be utilized as a strategic instrument for reducing policy-related risks and improving corporate performance. This study adopts a quantitative approach and applies Partial Least Squares Structural Equation Modeling (PLS-SEM) as the method for data analysis. The sample for the study was composed of 11 palm oil companies traded on the Indonesian Stock Exchange, for which comprehensive annual report data were available for the 2019-2023 period. These companies in the name of stock codes are specifically: AALI, ANJT, DSNG, BWPT, LSIP, PALM, SIMP, SGRO, SSMS, SMAR, and TBLA. The results of the analysis show that a company's value is significantly and positively influenced by macroeconomic factors, palm oil exports, and risk management practices. Of critical importance, the study identified environmental sustainability management as a key moderating factor, which amplifies the beneficial effects that both export activities and risk management have on company value. Transparent sustainability integration practices are essential to building resilience and driving long-term value.